Cloud infrastructure for HPC investment analysis - Santos, Maicon Ança dos; Cavalheiro, Gerson Geraldo H. (Revista de Informática Teórica e Aplicada, 2020)
With the consolidation of cloud computing technology, there is a growing interest in exploring it to support High Performance Computing (HPC). However, migrating such applications to public or private cloud environments brings some challenges, in particular, the cost in financing the migration process. In this paper, a literature review is presented with selected papers about analyzing cloud infrastructure investments. In particular, the selected papers analyse how investments impact applications. For discussion of related works, conditions for running HPC applications in the cloud are characterized.